Designing Mobile Application Dictionary Based on Students' Needs for Enhancing IT-Focused English Vocabulary - Riski Zulkarnain; Rahmat Saudi Alfathir; Richki Hardi; Mundzir , Mundzir; Lisda Hani Gustina; Wahyu Nur Alimyaningtias; Nove Kurniati Sari; Syaddam , Syaddam (Language Circle: Journal of Language and Literature, 2024)
The present study aims to design a mobile application dictionary that caters to students' needs for enhancing IT-focused English vocabulary. The study explores the effectiveness of the designed mobile application in improving students' IT-focused English vocabulary, their engagement in vocabulary learning, and their overall satisfaction with the application. This research aims to design a mobile application dictionary to enhance IT-Focused English Vocabulary. The study employs a mixed-methods approach, combining qualitative interviews and a quantitative survey, to understand the design requirements, implementation strategies, and effectiveness of the mobile application dictionary. The qualitative phase involves semi-structured interviews with IT students and subject matter experts to gain insights into the learners' challenges, preferences, and needs, as well as the crucial IT English vocabulary concepts. The quantitative phase evaluates the impact of the mobile application dictionary on IT students' vocabulary knowledge, confidence, and overall satisfaction through a survey. The integrated findings will provide a comprehensive understanding of the factors that contribute to the success of mobile application dictionaries in enhancing IT students' informatics English vocabulary, with practical implications for the development of similar language learning tools.